Zákon č. 301/2005 Z.z. Trestný poriadok s komentárom - Hromádková, Lucia
Zákon č. 301/2005 Z.z. Trestný poriadok v znení ďalších zákonov ... a zákonov č. 220/2011 Z.z., č. 262/2011 Z.z. a č. 331/2011 Z.z.